Penerapan Model Role Playing Terhadap Keterampilan Menyimak Teks Aural Siswa Kelas II Sekolah Dasar - Yawuru Nur Hasanah; Chandra; Inggria charisma (Institut Agama Islam Yasni Bungo Jambi Indonesia, 2026)
Listening skills in grade II students of SDN Padang City are still low, Most students are not focused and are still playing when their teacher is telling a story in front of the class. In addition, the lack of facilities and infrastructure at SDN Padang City is also a factor that hinders the creation of interesting learning. The general purpose of this study is to test the effect of using the role playing model on the listening skills of grade II students of SDN Padang City, where this model involves students to play roles in the stories they will listen to. The method used in this study is a descriptive qualitative method. Data were obtained through observation, testing and documentation. Based on the answers and processes during the learning process, the results of the study can be seen showing that there was a change in students' listening skills after using this role playing method. Keywords: Role playing, listening skills, elementary school